2010
DOI: 10.1016/j.neuron.2010.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Separable Learning Systems in the Macaque Brain and the Role of Orbitofrontal Cortex in Contingent Learning

Abstract: SummaryOrbitofrontal cortex (OFC) is widely held to be critical for flexibility in decision-making when established choice values change. OFC's role in such decision making was investigated in macaques performing dynamically changing three-armed bandit tasks. After selective OFC lesions, animals were impaired at discovering the identity of the highest value stimulus following reversals. However, this was not caused either by diminished behavioral flexibility or by insensitivity to reinforcement changes, but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

48
437
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(488 citation statements)
references
References 65 publications
48
437
2
1
Order By: Relevance
“…This fact, together with the absence of group difference in preoperative performance, meant direct comparisons could be made between mOFC lesions in the current experiment ( Fig. 2B) and lOFC lesions (9) (Fig. 2, Insets).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…This fact, together with the absence of group difference in preoperative performance, meant direct comparisons could be made between mOFC lesions in the current experiment ( Fig. 2B) and lOFC lesions (9) (Fig. 2, Insets).…”
Section: Resultsmentioning
confidence: 81%
“…S2). The schedules were identical to ones used to identify impairments in credit assignment after lOFC lesion (9). This fact, together with the absence of group difference in preoperative performance, meant direct comparisons could be made between mOFC lesions in the current experiment ( Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In support, Takahashi et al (2011) have recently shown that cocaine interferes with the ability of the orbitofrontal cortex to establish detailed state-space (Walton et al, 2010), which would lead to less accurate models and hence less accurate predictions. In the VOI account, increased cost of computation would have very similar effects, and cognitive impairments could be involved in the effect of stress (Schwabe and Wolf, 2009) and certainly the effect of dual tasks (Otto et al, 2013).…”
Section: Shifts Towards Model-free Learning In Addictionmentioning
confidence: 98%